Sacrococcygeal Tumor – A Rare Case Report - Wiwin Suhandri; Diki Riandi (Fakultas Kedokteran Universitas Riau, 2024)
Sacrococcygeal teratoma (SCT) is a rare congenital tumor primarily affecting infants, with a prevalence of approximately 1 in 35,000 live births. These tumors, often detected either prenatally or shortly after birth, originate from germ cells and typically occur at the base of the coccyx. Despite their benign nature, SCTs can pose significant risks to fetal and maternal health, necessitating careful management and monitoring. A 32-year-old primiparous woman presented to Siak Regional Hospital at 36 weeks of gestation with complaints of uterine contractions and bloody mucus discharge from the birth canal. A physical examination revealed a palpable mass in the uterine fundus and pubic symphysis. Ultrasonography confirmed the presence of a fetal SCT with a solid mass measuring 6.2 x 8.1 x 7.3 cm in the sacral region, and a cesarean section was performed. The infant, a baby girl, was born with a birth weight of 2150 grams and an Apgar score of 3/4. Congenital abnormalities were observed in the form of a solid mass around the sacrum, indicative of SCT. SCT poses challenges in prenatal diagnosis, management, and prognosis. Prompt recognition and multidisciplinary management are essential for optimizing outcomes. Further research is needed to enhance understanding and improve therapeutic strategies for this rare congenital anomaly. SCT is a rare congenital anomaly that requires early diagnosis. Thorough examination with ultrasonography is essential to rule out other congenital anomaly, and predict prognosis.